ANALISIS PENGGUNAAN MAJAS PADA PUISI BERJUDUL MEMOIR HITAM, LAGU HITAM, DAN SELEMBAR DAUN KARYA SONI FARID MAULANA - Ahmad Qori Fauzi; Ayu Yulia Sundari; Diena San Fauzia (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2018)
The objective of this study is to investigate the use of figurative language on poems written by Soni Farid Maulan. The method used in this study was descriptive qualitative approach. This study was conducted by understanding and analyzing figurative language in the poems. The result showed that Soni Farid Maulana’s poems had particular characteristic. The characteristic could be seen from the use of figurative language on his three poems. Furthermore, the figurative language consists of simile, personification, and metaphor.